2004
DOI: 10.1158/1078-0432.ccr-04-1071
|View full text |Cite
|
Sign up to set email alerts
|

Human Autologous Tumor-Specific T-Cell Responses Induced by Liposomal Delivery of a Lymphoma Antigen

Abstract: Purpose: The idiotype (Id) of the immunoglobulin on a given B-cell malignancy is a clonal marker that can serve as a tumor-specific antigen. We developed a novel vaccine formulation by incorporating Id protein with liposomal lymphokine that was more potent than a prototype, carrierconjugated Id protein vaccine in preclinical studies. In the present study, we evaluated the safety and immunogenicity of this vaccine in follicular lymphoma patients.Experimental Design: Ten patients with advanced-stage follicular l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 44 publications
0
41
0
1
Order By: Relevance
“…We also detected MAGE-A3-specific CD8 ϩ T cell responses in patients who developed the highest-titered broadly specific antibody responses after vaccination. So far, few trials have been conducted in which recombinant proteins were used as immunogen in cancer vaccines (12)(13)(14)(15)(16), and if T cell responses have been reported, they consisted mainly of CD4 ϩ T cells (17,18). Two reports have shown that vaccination with CT antigen NY-ESO-1 as a recombinant protein, formulated either with saponin-based adjuvant ISCOMATRIX or with cholesterol-bearing hydrophobized pullulan, induced strong antibody as well as CD4 ϩ and CD8 ϩ responses in the majority of patients (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…We also detected MAGE-A3-specific CD8 ϩ T cell responses in patients who developed the highest-titered broadly specific antibody responses after vaccination. So far, few trials have been conducted in which recombinant proteins were used as immunogen in cancer vaccines (12)(13)(14)(15)(16), and if T cell responses have been reported, they consisted mainly of CD4 ϩ T cells (17,18). Two reports have shown that vaccination with CT antigen NY-ESO-1 as a recombinant protein, formulated either with saponin-based adjuvant ISCOMATRIX or with cholesterol-bearing hydrophobized pullulan, induced strong antibody as well as CD4 ϩ and CD8 ϩ responses in the majority of patients (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Liposome is a delivery consisting of bilayer phospholipid, which is broadly used as various drug delivery systems. Liposome vaccine that carries idiotype protein and adjuvant cytokines for follicular lymphoma was developed (20,21). In a clinical trial using the vaccine combined with interleukin-2, both CD8 + and CD4 + T-cell immunities were induced along with specific antibody production (21).…”
Section: Discussionmentioning
confidence: 99%
“…Idiotype-specific T-cell cytokine responses, IFN-g enzyme-linked immunospot, and anti-idiotype antibody responses were measured as described previously (22,23).…”
Section: Methodsmentioning
confidence: 99%